1994
DOI: 10.1128/aem.60.10.3711-3717.1994
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-permeabilizing activities of Bacillus thuringiensis coleopteran-active toxin CryIIIB2 and CryIIIB2 domain I peptide

Abstract: Bacillus thuringiensis toxin CryIIIB2 exhibits activity against two agriculturally important pests, the Colorado potato beetle, Leptinotarsa decemlineata, and the Southern corn rootworm, Diabrotica undecimpunctata. CryIIIB2 shows significant structural similarity to Colorado potato beetle-active toxin CryILIA, whose crystal structure has been determined elsewhere [J. Li, J. Carrol, and D. J. Ellar, Nature (London) 353:815-821, 1991]. A clone limited to the putative 7-a-helical bundle domain I peptide of CryIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…The Cyt toxin family is distinct from the Cry family in a number of ways [1,3]. Only the Cyt toxins cause the cytolysis of a variety of eukaryotic cells and red blood cells (RBCs) in itro, even though both activated Cyt and Cry toxins can form pores in lipid bilayers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Cyt toxin family is distinct from the Cry family in a number of ways [1,3]. Only the Cyt toxins cause the cytolysis of a variety of eukaryotic cells and red blood cells (RBCs) in itro, even though both activated Cyt and Cry toxins can form pores in lipid bilayers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Cyt toxin family is distinct from the Cry family in a number of ways [1,3]. Only the Cyt toxins cause the cytolysis of a variety of eukaryotic cells and red blood cells (RBCs) in itro, even though both activated Cyt and Cry toxins can form pores in lipid bilayers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the three domains together make the insertion more stable, as observed for IE648, albeit with a lower critical insertion pressure than that of domain I alone. Von Tersch M. A. et al demonstrated that domain I of Cry3B2 is sufficient to induce ion leakage from phopholipid vesicles, but the efflux produced by the native toxin was greater than that produced by the domain I peptide (Von Tersch et al 1994). Walters et al also reported that the putative -helix bundle from domain I of Cry1Ac formed channels (Walters et al 1993).…”
Section: Discussionmentioning
confidence: 99%